2016
DOI: 10.18632/oncotarget.13193
|View full text |Cite
|
Sign up to set email alerts
|

Apocynin attenuates angiotensin II-induced vascular smooth muscle cells osteogenic switching via suppressing extracellular signal-regulated kinase 1/2

Abstract: Vascular calcification (VC) is a significant risk factor for cardiovascular morbidity and mortality. We recently reported that apocynin had benefits for preventing cardiovascular diseases. However, whether apocynin could attenuate VC is unknown. Here, we investigated the role of apocynin in VC and its underlying mechanisms. 163 participants with high or normal ankle–brachial index (ABI) were enrolled in this study for analyzing the demographic and biochemical data. In vitro, vascular smooth muscle cells (VSMCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…Transduced HASMCs with adenovirus expressing RAGEs induced ALP, calcium deposition and osteogenic differentiation defined by an increase of Msx and BMP2 expression [55]. However, others’ and our findings indicated that administration of different antioxidants like apocynin could significantly ameliorate diabetes-induced calcification [56, 57]. Importantly, the expression of β-catenin was shown to increase with the AGEs concentrations augment in AGEs-induced VSMC calcification, suggesting that there was a cross-talk between AGEs and Wnt/β-catenin signaling pathways [58].…”
Section: Advanced Glycation End Products (Ages) Signaling Pathwaysmentioning
confidence: 88%
“…Transduced HASMCs with adenovirus expressing RAGEs induced ALP, calcium deposition and osteogenic differentiation defined by an increase of Msx and BMP2 expression [55]. However, others’ and our findings indicated that administration of different antioxidants like apocynin could significantly ameliorate diabetes-induced calcification [56, 57]. Importantly, the expression of β-catenin was shown to increase with the AGEs concentrations augment in AGEs-induced VSMC calcification, suggesting that there was a cross-talk between AGEs and Wnt/β-catenin signaling pathways [58].…”
Section: Advanced Glycation End Products (Ages) Signaling Pathwaysmentioning
confidence: 88%
“…Consequently, more intracellular ROS production induced cell apoptosis and endothelium dysfunction [7,8]. Therefore, Ang II altered small artery structures and developed atherosclerosis [9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Another recently published work reported that b-aminoisobutyric acid induces osteoblast lineage (MC3T3-E1) differentiation and, when treated with NAC or APO, b-aminoisobutyric acid completely blocks the differentiation process (Zhu et al, 2018). In a study with rat vascular smooth muscle cell cultures exposed to calcification medium, the authors found that APO treatment (100 mM) blocks osteogenic phenotype markers (Feng et al, 2016). These findings strongly suggest that the role of ROS in bone remodeling is closely related to NOX activity.…”
Section: Discussionmentioning
confidence: 86%
“…They found that IL-17 blocks RANKL production and reduces TRAP-positive cells number in a NAC-dosedependent manner (Kim et al, 2017). In a study with rat vascular smooth muscle cell cultures exposed to calcification medium, the authors found that APO treatment (100 mM) blocks osteogenic phenotype markers (Feng et al, 2016). One-way ANOVA was used to analyze the statistical differences among groups, followed by the Tukey post hoc test.…”
Section: Discussionmentioning
confidence: 99%